2023
DOI: 10.3390/jcm12010377
|View full text |Cite
|
Sign up to set email alerts
|

Urine 3-Nitrotyrosine and Serum HDL as Potential Biomarkers of Depression

Abstract: Depression (MDD) is a leading psychiatric entity worldwide, with a high impact on individual life and public health. In recent years, efforts have been made to elucidate its biological underpinnings. MDD biomarker research provides promise for a better understanding of the biochemical processes involved in its pathogenesis. Oxidative and nitrosative stress (O&NS) and lipid disturbances are reported as major factors favoring the occurrence of depression. A total of 29 patients with MDD and 30 healthy volunt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
1
1
0
Order By: Relevance
“…It is related to the excessive activation of the enzyme indole 2,3-dioxygenase (IDO) catabolizing tryptophan to kynurenine and its metabolites [17]. Nevertheless, a study presented by Nobis et al showed similar results to the current study [66]. It can be only theorized that the increased levels of TRY in depressed patients may derive from the catabolic degradation of body proteins at the onset of depression/inflammation and TRY release.…”
Section: Discussionsupporting
confidence: 69%
“…It is related to the excessive activation of the enzyme indole 2,3-dioxygenase (IDO) catabolizing tryptophan to kynurenine and its metabolites [17]. Nevertheless, a study presented by Nobis et al showed similar results to the current study [66]. It can be only theorized that the increased levels of TRY in depressed patients may derive from the catabolic degradation of body proteins at the onset of depression/inflammation and TRY release.…”
Section: Discussionsupporting
confidence: 69%
“…In our recent work (22), we posited that the causal marker of oxidative stress in adolescents with depressive disorder is NT. Nobis et al (40) found a decreased level of TRP and an increased level of NT in the urine of adult depressive patients by our results in children and adolescents. This supports our assertion that nitrosative stress also plays a role in the pathophysiology of depressive disorder (41).…”
Section: Metabolitesupporting
confidence: 68%
“…ONOO − nitrates tyrosine residues on proteins, generating 3-nitrotyrosine (3-NT), a biomarker of NO-dependent nitrosative stress. Urine levels of 3-NT are higher in depressed compared to non-depressed patients, implying that nitrosative stress is a major contributor to cytokine induced depression (115).…”
Section: Reactive Nitrogen Speciesmentioning
confidence: 98%